Globetrotting crops: A contribution by ICA and the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) to agricultural research - Álvarez, Diego A.; Andrade, Robert Santiago; Tohme, Joseph M.; Ocampo, John; González, Carolina (Bioversity International and the International Center for Tropical Agriculture, 2021)
Scientific research and technological development is the creative work resulting from the collaboration of multiple institutions, and this has existed for decades in a great synergy between the Colombian Agricultural Institute (ICA) and the Alliance of Bioversity and the International Center for Tropical Agriculture (CIAT). This collaboration has contributed significantly to the distribution and promotion of rice, forage, beans, and cassava genetic materials around the world with improved agronomic characteristics. It has also contributed simultaneously to the maintenance and conservation of the diversity of these crops. The Alliance’s breeding programs and genebank records show that both institutions have collaboratively distributed close to 400,000 genetic materials containing base germplasm, advanced lines, or improved varieties to countries around the world, following international standards and phytosanitary certification issued by ICA. The results show that the materials distributed have been requested by a wide range of institutions in different countries and for multiple purposes in research and agronomic engineering. Finally, in this document, we highlight the major achievements of ICA and the Alliance, which have contributed significantly to scientific research and food security worldwide.